Marmaduke Pickthall and the Translation of the Qur'an: A Study of the Literal Approach and Its Relevance in the Western Context - Kerwanto, K; Alie, Haidar; Lukman, Rifansyah; Ntshangase, Mohammed Xolile (QiST: Journal of Quran and Tafseer Studies, 2025)
Islam is one of the religions with the largest number of adherents in the world. Muslims, although they come from diverse backgrounds, are united by the teachings of the Qur'an which was revealed in Arabic. To meet the needs of understanding for non-Arab Muslims, translating the Qur'an into various languages is important, but must still maintain the authenticity and sanctity of the original text. One of the English translations of the Qur'an that is considered authentic and neutral is the work of Marmaduke Pickthall, a convert from England. In his work The Meaning of the Glorious Qur'an (1930), Pickthall uses a literal approach with a classic English style ala the King James Bible. The goal is for Western readers to feel familiar and be able to understand the text with a similar spiritual nuance. This study is a literature review (library research) with a qualitative method that aims to examine Pickthall's translation approach, the challenges he faced, and the influence of his work on English-language Islamic studies. The results show that although his translation has been criticized for its archaic language style and extreme literal tendencies, Pickthall's work remains an important reference and has made a major contribution to building bridges of cross-cultural understanding.